Thermal Infrared Imaging: Toward Diagnostic Medical Capability - Khan, Masood Mehmood; Arthur, Daniel (IEEE-EMBS, 2011)
Thermal infrared imaging (TIRI) employs a focal plane array (FPA) of infrared detectors, with associated optics and optoelectronics to remotely detect and topographically map thermal emittance. Thermal and optical properties of human physioanatomy are not fully understood yet confounding diagnostic interpretation of human TIRI's. Elucidation of the specific physical mechanism via which thermal emission arises from human anatomy in-vivo requires empirical investigation under objective clinical protocols. This paper characterizes the fundamental architecture of the clinical TIRI system with a view to facilitation of objective protocol development, elucidation of the mechanism/s of human thermal infrared emittance, and eventual validation of TIRI as a diagnostic medical tool. Relevant recent and ongoing empirical studies by the authors are also summarized.